Optimized steps in determination of malondialdehyde (MDA) standards on diagnostic of lipid peroxidation - Fauziah, Prima Nanda; Maskoen, Ani Melani; Yuliati, Tri; Widiarsih, Erlina (Padjadjaran Journal of Dentistry, 2018)
Introduction: Lipid peroxidation, one of the known indices of oxidative stress, is documented in various diseases. Secondary oxidation products such as malondialdehyde (MDA) is commonly measured to observe lipid peroxidation. In this study, a spectrophotometric method was evaluated to measure thiobarbituric acid reactive substances (TBARS) with high sensitivity. This study was aimed to optimisation standard of MDA using tetraethoxypropane (TEP) 97% (FW=220.3). Methods: The method is based upon the reaction of malondialdehyde (MDA) and TBA in the glacial acetic acid medium. MDA is a known biomarker of oxidative status in a biological system. This research consists of two phases: first, making a stock of TEP, and the second phase was testing the concentration of TEP for finding the standard curve of MDA before used in diagnostic of lipid peroxidation. Results: Result showed the concentration 1,875-60 uM of TEP could form a precise standard curve. Conclusion: This concentration of TEP can be used as a reference as the standard of control in diagnostic of lipid peroxidation using TBARS method.